Tränenschlauch und Lebensbuch: Syntax und Semantik von Psalm 56,9* - Seidl, Theodor (Old Testament essays, 2008)
The focus of this publication is on Psalm 56:9. The Masoretic text is analysed in a text-critical and syntactic manner and, where neces-sary, conjectured. The semantics of the individual lexemes used in this verse is then scrutinised. The manner in which these words are used in other Old Testament texts, as well as the images and meta-phors within which they occur, are discussed. The position and the intention of verse 9 within the context of the whole Psalm is subse-quently outlined.